2007
DOI: 10.1007/s00425-007-0657-1
|View full text |Cite
|
Sign up to set email alerts
|

New insights on sucrose metabolism: evidence for an active A/N-Inv in chloroplasts uncovers a novel component of the intracellular carbon trafficking

Abstract: The presence of sucrose (Suc) in plastids was questioned for several decades. Although it was reported some decades ago, neither Suc transporters nor Suc metabolizing enzymes were demonstrated to be active in those organelles. By biochemical, immunological, molecular and genetic approaches we show that alkaline/neutral invertases (A/N-Invs) are also localized in chloroplasts of spinach and Arabidopsis. A/N-Inv activity and polypeptide content were shown in protein extracts from intact chloroplasts. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 72 publications
3
84
0
Order By: Relevance
“…Nevertheless, the particular response of each NI during peach development and different postharvest treatments (Lara et al, , 2011 indicates that NI transcripts display particular roles that will require further analyses. This hypothesis is reinforced by the discovery of novel physiological functions (Roitsch and González, 2004) and compartmentalization of invertases (Vargas et al, 2008;Vargas and Salerno, 2010). On the other hand, an increase in SS and SPS2 levels was also detected during postharvest peach ripening (Fig.…”
Section: Metabolism During Ripening Of Dixiland Peach Fruit: Preparinmentioning
confidence: 91%
“…Nevertheless, the particular response of each NI during peach development and different postharvest treatments (Lara et al, , 2011 indicates that NI transcripts display particular roles that will require further analyses. This hypothesis is reinforced by the discovery of novel physiological functions (Roitsch and González, 2004) and compartmentalization of invertases (Vargas et al, 2008;Vargas and Salerno, 2010). On the other hand, an increase in SS and SPS2 levels was also detected during postharvest peach ripening (Fig.…”
Section: Metabolism During Ripening Of Dixiland Peach Fruit: Preparinmentioning
confidence: 91%
“…The cell wall (FRUCT1 and FRUCT2) and vacuolar (FRUCT3 and FRUCT4) invertases were amplified in 25 cycles with primers described by Tymowska-Lalanne and Kreis (1998). The expression profile of the cytoplasmic/neutral invertases was examined with primers developed by Vargas et al (2008) in 22 amplification cycles. The RbcS primer set was obtained from Laval et al (2002), and CAB2 was amplified with primers described by Delessert et al (2004), both in 18 amplification cycles.…”
Section: Rt-pcr Primers and Conditionsmentioning
confidence: 99%
“…These enzymes have long remained poorly studied, and for decades, A/N-Invs were believed to occur exclusively in the cytosol. However, recent studies clearly demonstrated the presence of A/N-Invs in various organelles in addition to the cytosol (Vargas et al, 2008;Xiang et al, 2011). It is now clear that A/N-Invs play an important role in plant development and stress tolerance (Barratt et al, 2009;Vargas and Salerno, 2010;Xiang et al, 2011).…”
mentioning
confidence: 99%